O Direito à segurança de renda e o Programa Bolsa Família: medidas de proteção e desproteção social no município de João Pessoa entre 2004 e 2014 - Domingos, Renata Martins (2015)
This thesis aims to analyze, from the perspective of social inclusion and human rights defense, how the right to income security, a facet of the right to social protection, is guarded by means of the Programa Bolsa Família (PBF - Family Allowance, a social welfare program of the Brazilian government). To achieve this, the characteristics of its management design are analyzed here, as well as the beneficiary families’ perception of the Program. This thesis is a case study of the PBF that focuses on the municipality of João Pessoa (Northeastern Brazil). It also analyzes how the Program, in the context of the supremacy of neoliberalism, interferes in the struggle for income and, consequently, in the affirmation of social rights. The citizenship profile of the beneficiary families was researched in this thesis based on the binomial right versus duty, which is embedded in its management design and in the conditionalities it requires, in the areas of health and education and, in the case of existence of child labor, also in the scope of social assistance. Although they are included in the law that instituted the Program as forms of monitoring the public policies of education and health, the conditionalities are used to punish the beneficiary families, as the payment of the pecuniary benefit is suspended when they are not fulfilled. Therefore, one of the Program’s principles is that the families are responsible for the situation of poverty in which they live. Having as historical background and heritage the option made by the Federal Government, in the 1990s, to apply the recommendations of international financial agencies to the conduction of social policies, the Program is included in the scope of activation policies or workfare. In this sense, the management of the Program shows ambiguities. Its creation gives visibility to Brazil’s poor families - an important step towards their recognition as members of the society in a situation of vulnerability (recognition by right). However, on the other hand, admission to the Program requires that the families declare income destitution, which moves them away from the condition of citizens towards that of consumers. Furthermore, the regulation of penalization due to unfulfilled conditionalities indicates that they serve as a political justification of the Federal Government for granting income with no link to work, which guarantees legitimacy, in society, for the Program’s permanence. The neoliberal limits contained in the Program’s principles also delimit the pecuniary benefits provided by it, in the scope of its legal framework, when they provide it with the status of a contingent right. However, as the income becomes an important monetary complement to the families, is used for a long period and enables them to improve their life conditions and certainties, especially regarding food increment, the beneficiary families appropriate it as their right, corroborating the historical trajectory of affirmation of social rights.